Le canard était toujours vivant ! De Troppmann à Weidmann, la fin des complaintes criminelles, 1870-1939 - Jean-François “Maxou” Heintzen (Criminocorpus)
Against the commonly accepted idea according to which criminal laments would have disappeared from France at the end of the 19th century, and replaced by the “short news items” column in popular dailies, the present article follows their transformation until the eve of World War II. With a corpus of mainly provincial broadsheets we examine the evolution of the lament paper copy, of its underlying melody, of its style and content, and also of its publishing and trading. So we will follow the art of “singing the crime” over a half-century, from the lament to the “realistic song with a criminal character”, from the crime of Pantin to the latest “serial killer” of the interwar period.